A comparative study of entrepreneurship education between Singapore and Taiwan. Issue 7 (21st August 2017) - Yu, Min-Chun; Goh, Mark; Kao, Hao-Yun; Wu, Wen-Hsiung
Abstract : Purpose: For entrepreneurship education issue, the purpose of this paper is to apply a novel four-step method of comparative education research and assessment items for university-based entrepreneurship ecosystems (U-BEEs), with a specific focus on universities in Taiwan and Singapore. In this paper, entrepreneurship education development is explored, and important implications for the further improvement of entrepreneurship education are provided. Design/methodology/approach: This study is based on the comparative education research method and proceeds in four steps (i.e. description, interpretation, juxtaposition, and comparison). The U-BEE items are applied to exemplify the similarities and differences of the process by which entrepreneurship education developed in two universities each in Singapore (National University of Singapore and Nanyang Technological University) and Taiwan (National Taiwan University and National Tsing Hua University). Findings: From the country-based standpoint, the findings include considering broader factors (i.e. history, education) in such a comparison of the similarities and differences among four universities, reflecting the reality in the Asian region and introducing the method application of comparative education research for the first time in entrepreneurship education. From holistic and specific perspectives of U-BEE, the findings consist of presenting similarities and differences based on the comparisons of each item and showing the classified findings. Originality/value: This study provides helpful insights based on the perspectives of academics and practitioners. First, the authors urge the necessity of the theoretical base of teaching and learning in education when universities plan for entrepreneurship education. Second, the authors stress the critical impact of the government on the execution of entrepreneurship education in the higher education context.